(3GdKeQI ` aj Yde CMcGe GdfLhes - (3HWdejhS GdMcjes
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf eWdY cJGH GdKeQI dHWdjehS GdMcje JeGe GdcJH GdCQHYI GdJi CdagG ai GdCMcGe dShQS JdejPg bGd (B: (3bO bOefG dc jGShQS cJHkG ajeG JDKQg GdchGcH ai YGde GdJQcjH s
(3BNQgG (B:s
(3jchf ef GdeZQH Edi GdeTQb , aEf GdNGQLi jCJi ef HYjO Edi GdEbdje hEf de jcf SGFQkG , aEf GdNGQLi ef MVQI GdEbdje JQLeI Je cJGH GdKeQI GdeSeGI HGdQhejI GHWQhecG , heYfGg hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B8s
(3HgG fXGe GdJYbjHIs
(3eY TQMgG HGdaGQSjI dfUjQ GdOjf GdWhSi GdeJhai (B672(3g`s
(3cJHJ Hbde bdjd GdVHW heged GdfbW CMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B670 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs